1998
DOI: 10.1046/j.1365-2672.1998.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an in vitro methodology to determine the transit tolerance of potentially probiotic Lactobacillus and Bifidobacterium species in the upper human gastrointestinal tract

Abstract: An in vitro methodology which mimics in vivo human upper gastrointestinal transit was developed. The transit tolerance of potentially probiotic Lactobacillus and Bifidobacterium species was determined by exposing washed cell suspensions at 37°C to a simulated gastric juice (pH 2·0), containing pepsin (0·3% w/v) and sodium chloride (0·5% w/v), and a simulated small intestinal juice (pH 8·0), containing pancreatin USP (1 g l−1) and sodium chloride (5 g l−1), and monitoring changes in total viable count periodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
415
3
27

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 643 publications
(472 citation statements)
references
References 29 publications
27
415
3
27
Order By: Relevance
“…O acúmulo de prótons no meio intracelular pode interferir no funcionamento da membrana celular, prejudicando processos essenciais à sobrevivência celular (Guchte et al, 2002). (Charteris et al, 1998b). A sensibilidade a sais biliares no intestino delgado ocorre, principalmente, pela ação detergente deles à membrana celular constituída de lipídeos e ácidos graxos das bactérias (Guchte et al, 2002 (Charteris et al, 1998b;FAO/WHO, 2002).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O acúmulo de prótons no meio intracelular pode interferir no funcionamento da membrana celular, prejudicando processos essenciais à sobrevivência celular (Guchte et al, 2002). (Charteris et al, 1998b). A sensibilidade a sais biliares no intestino delgado ocorre, principalmente, pela ação detergente deles à membrana celular constituída de lipídeos e ácidos graxos das bactérias (Guchte et al, 2002 (Charteris et al, 1998b;FAO/WHO, 2002).…”
Section: Resultsunclassified
“…O antibiograma foi realizado em duplicata, com três repetições, de acordo com a técnica adaptada de susceptibilidade a antimicrobianos por difusão da droga em discos (Charteris et al, 1998b). As amostras de microrganismos isolados e selecionados foram cultivadas em ágar MRS (Difco, Detroit, Estados Unidos), em aerobiose (37ºC, 24 a 48h).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…In vitro simulation has suggested that whereas some species of L. and B. lose viability during gastric transit, ingestion with milk proteins improves their tolerance to the pH of upper GI system (Charteris, 1998). In addition to its potential effect on bacterial viability, milk has been hypothesized to contain components such as 3-hydroxymethyl glutarate and orotic acid that may independently lower cholesterol (Mann, 1977;St-Onge et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…and Bifidobacterium spp. showed a loss of viability when exposed to the secretions of stomach acid and bile salts 32 . However, an increase of CFU was observed in these bacteria in the stools of individuals who ingested them, which could act beneficially in patients [13][14]33 .…”
Section: Conflict Of Interest Referencesmentioning
confidence: 99%